Ceferino Mapuche: La Hora del Santo - Dagotto, Adrian (Argentina)
The analysis and reflection of a unique historical event, produced with the remnants of the "Big Bang Cultural Religious" between the spiritual tradition of native people and the Western "civilizing religious model."
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films